PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI KEBERMANFAATAN DAN PERSEPSI KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN E-COMPLAINT (Studi kasus pada Mahasiswa Universitas Brawijaya) - Nur Syamsan Fajrina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to determine the effect of perceived ease of use, perceived usefulness and perceived trust to intention to use e-complaint. The research was conducted qualitatively with survey approach. Sample this study was students of Universitas of Brawijaya force 2012 until 2016 who have used e-complaint which amounted to 98 people. Data were analyzed by multiple linear regression analysis. The results showed that the perceived ease of use had a significant and positive influence on the intention to use e-complaint. Perceived usefulness had a significant and positive influence on intention to use e-complaint. Perceived trust had a significant and positive influence on intention to use e-complaint.Keywords: ease of use, usefulness, trust, intention to use